Design and Implementation of Online Problem Based Learning (PBL) Assisted by Innovative Media to Improve Elementary School Student Learning Outcomes - Agung Ratih Rosmilasari, Desak Made; Adoe, Dean Putra (Journal of Education Technology, 2020)
During the Covid-19 pandemic, online learning implementation in elementary schools experienced problems in delivering material to students. The use of fully online learning methods causes learning difficulties, so that it has an impact on decreasing student learning outcomes. To overcome this problem, the purpose of this study is to apply the Problem Based Learning model assisted by innovative media in class II students to improve learning outcomes in thematic learning. This research is a classroom action research that is designed in two cycles. Each cycle has four stages, namely, planning, action, observation/evaluation, and reflection. One cycle is carried out for three meetings, namely two meetings to implement learning and one meeting to implement learning outcomes tests. During the research, the learning outcome data were measured using multiple-choice tests, and the learning process was measured using the observation method. Data in the form of scores were analyzed using descriptive statistics, and observational data were analyzed qualitatively. The results showed that the classical mean score in cycle I was 81.91% (high category), and there was an increase in cycle II with a classical mean score of 91.13% (very high category). Thus, the online PBL model assisted by innovative media can improve student learning outcomes.